Modeling the Electrodynamics of Cellular Uptake of Nanoparticles at Drug Delivery Strategies - Nieto-Chaupis, Huber (2022)
Based at the proposal of Hauert-Berman-Nagpal-Bhatia Model, this paper has developed a physics-based theory that encompasses with this model in order to study the problem of expelling of delivered nanoparticles. The derived equations have yielded scenarios where analogue RC circuits and the constant of diffusion acquire valid as well as invalid values. A final formulation by taking into account the cylindric geometry that would adapt to the case where nanoparticles receptors complexes are expelled from target cells is presented. With this the computational reconstruction of diffusion's constant is presented.